O probabilismo na scholastica colonialis segundo Diego de Avendaño - Casarin, Régis Franco (Universidade do Vale do Rio dos Sinos, 2012)
This is a historical-epistemological study on the XVII-XVIII century's probabilism developed in Colonial America, especially in Peru, based on Diego de Avendaño's first volume of his Thesaurus Indicus. It is divided into three sections: Background; moral tension in the colonies, and the Thesaurus Indicus . Besides seeing the historical significance and influence of this moral system in the Spanish colonies, enters into the problem of moral systems, with particular emphasis on probabilism and exposes as an illustration, not without knowing a little of Diego de Avendaño, the management of justice in the Indias, reported in Volume I of the Thesaurus . We conclude that the work in study is totally permeated by the probabilism.
Keywords: Probabilismo; Diego de Avendaño; Escolástica colonial; Probabiliorismo; Tuciorismo; Probabilism; Colonial scholastic; Probabiliorism; Tuciorism; ACCNPQ::Ciências Humanas::Filosofia